Tubular Colonic Duplication with Anorectal Malformation Recto-Vestibular Fistula: A Case Report - Fitriansyah, Muhammad Noor; Sanden, Ken; Soenjoto, Dadik Agus (Syntax Literate, 2025)
Anorectal malformations associated with colonic duplications are a rare condition. Double terminations of tubular colonic duplication with Anorectal Malformation are even rarer. Colonic duplication may have different presentations according to its location and size and incidence of less than 15% of all gastrointestinal duplications. These cases also illustrate the diagnostic challenge and variable presentation of colonic duplications in female patients with recto-vestibular fistula. This report aims to present and analyse the clinical presentation, diagnostic approach, and management of anorectal malformations associated with colonic duplications highlighting the challenges and treatment strategies for such a rare case. Case Presentation: We present the case of an 11-month-old female referred from a network hospital with a history of stool leakage from genital, status post diverting colostomy at age of 4 month and was referred to our center for further evaluation and treatment. During the procedure of diverting colostomy, colonic duplication was identified at the colostomy site. Further radiographic evaluation and exploratory laparotomy with complete resection of the colonic duplication was performed. Conclusion: Colonic duplication is a rare congenital disorder, with an even rarer association with anorectal abnormalities. This condition presents with diverse clinical manifestations, necessitating a thorough preoperative differential diagnosis. Surgical intervention remains the treatment of choice, with complete resection being the preferred approach for cystic, diverticular, and short tubular duplications. However, total colon duplications may require alternative management strategies.